2016
DOI: 10.1002/jor.23245
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a novel osteosarcoma cell line: CHOS

Abstract: Osteosarcoma has a well-recognized bimodal distribution, with the first peak in adolescence and another in the elderly age-group. The elderly patients have different clinical features and a poorer prognosis as compared to adolescents. To better understand the biological features of osteosarcoma in the elderly population, we established a new human osteosarcoma cell line from a 58-year-old man with primary chondroblastic osteosarcoma. After 6 months of continuous culture in vitro for over 50 passages, an immort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…While most of the previously established OSA cell lines including HOS, MNNG‐HOS, KHOS, U2OS, and MG63 were derived from the primary tumor, this OSA 1777 cell line was established from the recurrent conventional OSA (Supplementary Table S1) . As there are no specific proteins or genetic markers for OSA confirmation, the principal diagnostic tool that remains is histologic examination and patient history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the previously established OSA cell lines including HOS, MNNG‐HOS, KHOS, U2OS, and MG63 were derived from the primary tumor, this OSA 1777 cell line was established from the recurrent conventional OSA (Supplementary Table S1) . As there are no specific proteins or genetic markers for OSA confirmation, the principal diagnostic tool that remains is histologic examination and patient history.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the previously established OSA cell lines including HOS, MNNG-HOS, KHOS, U2OS, and MG63 were derived from the primary tumor, this OSA 1777 cell line was established from the recurrent conventional OSA ( Supplementary Table S1). [7][8][9][10][11][12][13][14][15][16] As there are no specific proteins or genetic markers for OSA confirmation, the principal diagnostic tool that remains is histologic examination and patient history. As shown in Figure 1, the H&E stain of recurrent tumor tissues was consistent with highgrade OSA and showed typical anaplastic osteoblasts elaborating osteoid matrix; there was 30% tumor necrosis after second-line chemotherapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers showed that cardiomyocyte viability decreased in a dose-dependent manner in diabetic cardiomyopathy after treatment with AGEs. 32 In addition, Liu et al 28 reported that AGEs significantly decreased chondrocyte viability. Similarly, studies by other researchers have shown that decreases in chondrocyte viability occurred after treatment with AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was detected by Cell Counting Kit-8 (CCK-8, Dojindo, Japan), as described previously. 28 The cell densities were 5 × 10 3 cells/well for CCK-8. After being seeded in 96-well culture plates, AF cells were treated with AGEs at various concentrations for 3d.…”
Section: Methodsmentioning
confidence: 99%
“…Equal amounts of protein samples were subjected to 10–12% SDS-PAGE separation and then transferred to the polyvinylidene difluoride membrane (Millipore, Boston, MA, USA). Subsequent procedures were performed as described previously [38] . The following antibodies were used: rabbit anti-PARP-1 (1: 500, Santa Cruz, CA, USA), rabbit anti-AIF (1:1000, Abcam), rabbit anti-LC-3 (1:1000, Sigma-Aldrich), rabbit anti-p62 (1:1000, Cell Signaling Technology, MA, USA), mouse anti-PAR (1:1000, Enzo Life Sciences), mouse anti-β-actin (1:5000, Abbkine), rabbit anti-COX Ⅳ (1:1000, Proteintech, Wuhan, China), mouse anti-Histone H3 (1:3000, Abbkine), HRP-conjugated secondary antibodies (1:5000, Abbkine).…”
Section: Methodsmentioning
confidence: 99%